A few remarks to the van der Waals equation - Jana Kalová, Radim Mareš (Littera Scripta, 2011)
In 2010 it was 100 years since the time when Johannes Diderik van der Waals was awarded the Nobel Prize „for his work on the equation of state for gases and liquids“. Van der Waals equation is included in all modern and less modern physics, technical thermodynamics and physical-chemistry textbooks. This equation surprisingly well qualitatively describes phase transitions. It is a connection between the ideal gas behavior description and between a description of real liquids and gases. This paper deals with a description of the van der Waals equation in pressure, temperature and density variables. The Maxwell’s rule using the density is presented. Isotherms, the spinodale and the limit curve for specic equation of state parameters are shown in a diagram. It is shown that p – p and p – v diagram is strongly schematic presented in many textbooks. Problems involving the numerical solution of the limit curve values using Maxwell’s rule and an importance for a good initial guess choice are discussed.